Do Teatro aos Quadrinhos: um estudo semiótico da tragédia de Romeu e Julieta. - Curvelo., Amanda Carvalho Mendes (2013)
Recently, the graphic novels authors have been interested in adapting works of the literary canon. The world-famous tragedy Romeo and Juliet, written by William Shakespeare in 1595, was translated over time for different artistic languages, including the Comics language. This transposition of signs, from an art form into another, is known as intersemiotic translation. According to Jakobson (1995: p.65), intersemiotic translation means the interpretation of verbal signs through the non-verbal signs systems. Later, Plaza (2003) based on Jakobson work adds that the intersemiotic translation can also be applied from a sign system to another, for example, the verbal art to the music, dance, film or painting. Therefore, in order to study this transposition process into comics, we have selected three Romeo and Juliet adaptations, raised from different cultures a British, a Japanese and a Brazilian ones. Supported by the theories of Semiotics of Culture, Peircean semiotics, the theory of carnivalization and theory of adaptation, this research is going to investigate how the signs of theatrical language were translated into the language of comics, and also the influence of culture on these semiotic operations.